Geotechnical Investigation to Predicte of Liquefaction Potential in Gunung Pangilun Area, Padang City - Fachriansyah, Ikrar; Raihan, Shufrael; Putra, Hendri Gusti; Andriani (Universitas Islam 45, 2025)
Gunung Pangilun is an area in Padang that continues to experience urban and infrastructure development. Padang City is located in an earthquake-prone area in Indonesia, so it has a high risk of liquefaction. Geotechnical investigation is a crucial step in assessing liquefaction potential. This study aims to predict the liquefaction potential in Padang City, especially in the Gunung Pangilun area. The research methodology includes collecting geotechnical data through soil testing in the field, namely CPT and laboratory testing in the form of soil physical property tests. Liquefaction potential analysis was carried out using empirical methods such as the Seed & Idriss and Tsuchida methods. The analysis showed that at CPT points 1, point 2, point 3, and point 4, there was potential for liquefaction at depths below 1.0 m and 2.0 m. Meanwhile, based on the Tsuchida Curve, it shows that the surface of the soil (depth of 0.00 m - 1.00 m) does not have the potential for liquefaction because it is outside the liquefaction zone and the sand has a non-uniform gradation. Analysis of grain gradation on the ground surface (depth 0.00 m - 1.00 m) has a D50 value of 1.62 mm and at a depth of 1.00 m has a D50 value of 1.39 mm so that at that point, it shows that the ground surface has no potential for liquefaction. The conclusion of this study shows that the potential for liquefaction on Gunung Pangilun is at a depth of more than 1 m.